Exploring the school management team's competencies in curriculum management at Phokwane Circuit Primary Schools, Limpopo - Nkadimeng, Mampuru Philemon (My University, 2017)
Satisfactory learners′ performance in primary schools is faced by many challenges. One of these challenges is the School Management Teams′ (SMTs) competencies in the management, leadership, administration, monitoring and assessment of curriculum implementation. In an attempt to contribute towards improving the learners′ performance, this research study focused on exploring the SMTs′ competencies in the management, leadership, administration, monitoring and assessment in the management of curriculum implementation. The main focus group of the study was the heads of department (HODs) due to the fact that they are deemed as curriculum managers and are therefore well positioned to ensure successful curriculum implementation which yields good learners′ performance in schools. A qualitative case study design was adopted to explore the SMTs curriculum management competencies. This design was used because of its ability to document multiple perspectives, exploring contested viewpoints, its usefulness for exploring and understanding the process and dynamic of change as well as its potential to engage participants in the research process (Simon, 2009:23). The case study allowed the researcher to use interviews and document study in the case schools as sites of the research study and hence this facilitated triangulation. Interviews and document study were used as methods of collecting data from the participants. The population of the study was composed of 88 SMT members from 22 primary schools in Phokwane Circuit, Limpopo Province. Four primary schools were purposively sampled and from each of the schools four members of SMT namely, the principal, deputy principal and two HODs formed the study sample. The total study sample was therefore sixteen. Data collected was then analysed by content analysis method of analysis. The research findings revealed that the SMTs and HODs in particular lack competencies in the management, leadership, administration, monitoring and assessment of curriculum implementation. The study further revealed that there was lack of teamwork among members of SMTs, overcrowding of learners and v insufficient of learner and teacher support materials (LTSM) in the primary schools. The study therefore recommended that the SMTs and HODs in particular be extensively trained in the management, leadership, administration, monitoring and assessment through unique, intensive and well-tailored programmes by service providers. Furthermore, the study recommended that the HODs be thoroughly developed in educational legislative frameworks and policies in order to ensure appropriate application of the documents.
Thesis (M.A. Education (Educational Studies)) -- University of Limpopo, 2017
Keywords: Learner performance; Primary schools; School management teams; School-based management; Curriculum enrichment; School management teams; Education, Primary -- South Africa -- Limpopo